Behavioural and biological risk factors of non-communicable diseases among adults in Cabo Verde: a repeated cross-sectional study of the 2007 and 2020 national community-based surveys - Pengpid S. (2023)
OBJECTIVE: The aim of the study is to estimate trends in the prevalence and associated factors of non-communicable disease (NCD) risk factors in adults from 2007 to 2020 in Cabo Verde. DESIGN: Population-based cross-sectional study. SETTING: Nationally representative samples of adult population in Cabo Verde from the 2007 and 2020 STEPwise approach to NCD risk factor surveillance (STEPS) surveys. PARTICIPANTS: The sample included 1760 adults in 2007 and 3721 in 2020. OUTCOME MEASURES: Included fruit/vegetable consumption, low physical activity, sedentary behaviour, current tobacco use, hazardous alcohol use, diabetes, total elevated cholesterol, hypertension and overweight/obesity. Logistic regressions adjusted for sociodemographic factors were applied to estimate predictors of each of the nine NCD risk factors. RESULTS: Compared with participants in the study year 2007, participants in the study year 2020 had a significantly higher prevalence of low physical activity (adjusted OR (AOR): 2.21, 95% CI: 1.15 to 4.25) and overweight/obesity (AOR: 1.68, 95% CI: 1.26 to 2.23) and significantly lower rate of hypertension (AOR: 0.77, 95% CI: 0.64 to 0.93). Low physical activity (AOR: 1.61, 95% CI: 1.23 to 2.10), overweight/obesity (AOR: 2.59, 95% CI: 2.10 to 3.20), current tobacco use (AOR: 1.94, 95% CI: 1.36 to 2.75), hypertension (AOR: 5.45, 95% CI: 4.24 to 7.00), diabetes (AOR: 8.40, 95% CI: 4.65 to 15.18) and elevated total cholesterol (AOR: 4.58, 95% CI: 2.83 to 7.39) were more common among the 50-64-year-olds. Being male increased the odds of current tobacco use (AOR: 3.64, 95% CI: 2.75 to 4.81) and hazardous alcohol use (AOR: 4.79, 95% CI: 3.15 to 7.27), and decreased the odds of low physical activity (AOR: 0.48, 95% CI: 0.39 to 0.58) and overweight/obesity (AOR: 0.47, 95% CI: 0.40 to 0.56). CONCLUSIONS: Of the nine NCD risk factors evaluated from 2007 to 2020 in Cabo Verde, two increased (overweight/obesity and low physical activity) and one decreased (hypertension). Several associated variables were identified for each individual NCD risk factor that can help in guiding interventions.